The effects of cephalexin on fracture healing in a rat femur fracture model - Uslu, Muhammed; Yilmaz, Bilal; Mraja, Hamisi Mwarindano; Dasci, Mustafa Fatih; Sarac, Elif Yaprak; Kucukyildirim, Bedri Onur; Gulec, Mehmet Akif; Yuksel, Serdar (TURKISH JOINT DISEASES FOUNDATION, 2023)
Objectives: The aim of this study was to examine the effects of cephalexin on the fracture union histomorphometrically, radiologically, biomechanically, immunohistochemically, and histopathologically in a rat femur fracture model and to evaluate the effects of the antibiotics to be used in the prophylaxis of fracture infection on the union of the fracture.Materials and methods: A total of 48 male Wistar rats were divided into four groups as two-week control (C2) and cephalexin (CEP2) and four-week control (C4) and cephalexin (CEP4). After establishment of standard fracture model on right femurs, 60 mg/kg/day of cephalexin was applied to CEP2 and CEP4 by oral gavage. Radiological, biomechanical, histopathological, immunohistochemical, and histomorphometric examinations were performed on amputated femurs.Results: Callus volume of CEP4 group significantly increased compared to CEP2 group (p=0.005), while no significant difference was found in the bone mineral density and callus/bone volume among the groups (p>0.05). There was no significant difference in flexural strength between the C4 and CEP4 groups (p=0.093). Histological healing scores increased from Week 2 to Week 4 (p=0.002) and inflammation scores decreased in both control and cephalexin groups (p=0.010 and p=0.008); however, no significant difference was found in healing and inflammation scores (p>0.05). The CD34+ immunoreactivity in the CEP2 group was significantly higher than the C2 group (p=0.029). Collagen type III level was significantly lower in the CEP2 and CEP4 groups compared to the corresponding control groups (p=0.008 and p=0.016, respectively).Conclusion: Cephalexin did not exert any radiological, histopathological, histomorphometric, biomechanical, and immunohistochemical adverse effects on the femoral fracture healing model in rats; however, it showed positive effects on CD34 and Collagen type III levels. Based on these findings, antibiotherapy with cephalexin may be considered as a safe treatment for fracture union.
Keywords: Cephalexin; femur; fracture healing; rat; IN-VIVO; BONE; ANTIBIOTICS; INHIBITION; LEVOFLOXACIN; CEFUROXIME; CEFAZOLIN; CELLS; Orthopedics; Surgery